PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN MOTIVASI TERHADAP KINERJA PEGAWAI PADA KOMISI PEMILIHAN UMUM DAERAH KOTA TANGERANG SELATAN - Muger Apriansyah; Ibrahim Bali Pamungkas; Wahyu Andri Wibowo (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2021)
The purpose of this study was to determine the positive and significant influence partially or jointly Transformational Leadership and Motivation on the performance of the General Election Commission employees of South Tangerang City. The object of this research is all employees in the South Tangerang Regional Election Commission. The type of research used in this research is explanatory research or explanatory research. Explanatory research is research that intends to explain the position of the variables studied and the relationship between one variable and another. Methods of data collection using observation and questionnaires. Sampling technique using simple saturated with the number of respondents as many as 40 employees. The validity of the data in this study used Validity Test, Reliability Test, and Classical Assumption Test. The result of this study is that there is a positive and significant influence partially or simultaneously between Transformational Leadership and Motivation on the performance of the Regional Election Commission employees of South Tangerang City